Modern approaches to the choice of antimicrobial agents for pelvic inflammatory diseases: the role of innovative microbiological methods - О. А. Бурка; Т. М. Тутченко; Н. Ю. Педаченко; О. М. Кудлай (Publishing House TRILIST, 2020)
Pelvic inflammatory diseases (PID) is comprehensive term that includes infectious-inflammatory lesions of the endometrium, fallopian tubes and ovaries. PID is one of the main causes of treatment of reproductive aged women by gynecologists, and the cause of impaired reproductive function, chronic pelvic pain syndrome and ectopic pregnancy in the absence of treatment. This article provides an overview of current clinical guidelines for diagnosis and general treatment approaches of PID. A detailed analysis of modern scientific researches dedicated to the change of the PID's pathogens structure and the peculiarities of their clinical presentation today. This analysis showed that despite the leading role of sexually transmitted infections, opportunistic flora is of great importance in the pathogenesis of this pathology. Features of the PID's clinical course include an increase in the recurrence frequency. These features are associated with the growing worldwide phenomenon of antibiotic resistance. Data from the European Antimicrobial Resistance Surveillance Network report at the European Center for Disease Control "Antibiotic Resistance Surveillance 2017" on the resistance prevalence of clinically relevant pathogenic bacteria to the most commonly used antimicrobials. Nonspecific bacterial pathogens of PID in the European region show a fairly high rate of antibiotic resistance. At the same time, the experience of many countries demonstrates the effectiveness of the strategy of antimicrobial stewardship strategy, one of the main principles of which is microbiological research whenever possible when prescribing antibacterial therapy. Thus regardless of whether representative of the opportunistic flora is a direct cause of a severe PID course or secondary due to previous sexually transmitted diseases, its identification and antibiotic susceptibility testing is critical for the effective treatment of PID (especially severe forms) given the prevalence of antibiotic resistance.